Российские театры: взаимосвязь моделей финансирования и целей политики в области театральной деятельности - Борис Рудник (Вопросы государственного и муниципального управления, 2018)
The paper considers the transformation of the public funding mechanisms of theatres during the period from the last years of the USSR and early years of post-Soviet Russia up to the present. It analyses the differences between models applied at different times.Several parameters of these models are taken into consideration, including the requirements that public bodies impose on the activities of theatres due to funding, and special features of budgetary tools which among other things characterize the approach to the determination of amounts of funding transferred to the theatres. Four models of public funding are juxtaposed with the state cultural policy objectives in theatrical activity set by the Constitution of the Russian Federation and federal statutory and regulatory enactments. The hypothesis that there is no direct orientation towards such objectives is put forward and fi nds its confi rmation. A new model based on the public grants mechanism that meets the requirement of being policy objective-oriented is proposed.